2013
DOI: 10.3810/pgm.2013.01.2627
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Considerations of the Pharmacokinetics and Clinical Use of Extended-Release Opioids in Treating Patients with Chronic Noncancer Pain

Abstract: Extended-release (ER) opioid analgesics are associated with prolonged analgesia and greater stability in pain relief compared with immediate-release formulations. Due to the pharmacokinetic (PK) characteristics of ER opioids and additional clinical advantages, the use of ER opioids for patients with moderate-to-severe chronic noncancer pain has increased. Primary care physicians are the major prescribers of opioids and require an in-depth understanding of the risks and benefits of opioid treatment in pain mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Compared with IR opioid formulations, ER opioid formulations are more appropriate to achieve optimal pain control for patients with chronic persistent pain requiring around-the-clock analgesia [ 2 ]. The quality of ER formulations can be partially evaluated by assessing the three cebranopadol PK parameters, t max , HVD and PTF, highlighted above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with IR opioid formulations, ER opioid formulations are more appropriate to achieve optimal pain control for patients with chronic persistent pain requiring around-the-clock analgesia [ 2 ]. The quality of ER formulations can be partially evaluated by assessing the three cebranopadol PK parameters, t max , HVD and PTF, highlighted above.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids represent effective analgesics with a broad spectrum and are used in acute and chronic pain conditions [ 1 ]. In clinical practice, extended-release (ER) opioids are used more often for the treatment of moderate-to-severe chronic pain in noncancer patients [ 2 ]. Despite the clinical benefits of these strong analgesics that act via μ-opioid peptide (MOP) receptor agonism, concerns have been expressed about the safety of long-term opioid administration.…”
Section: Introductionmentioning
confidence: 99%
“…ER opioid formulations are considered more suitable for appropriate management of pain in chronic patients. Oral intake of ER medicinal products produces higher plasmatic concentrations and lower peak-to-trough changes over the dosing interval, in comparison with IR products ( Gudin, 2013 ; Nicholson, 2013 ). The first formulation having, according to FDA, abuse-deterrent characteristics contained only hydrocodone bitartrate was a once-daily hydrocodone bitartrate ER product, prescribed for the long-term opioid treatment of severe pain refractory to other analgesic strategies ( Dhillon, 2016 ).…”
Section: Hydrocodone In the Medicinal Productsmentioning
confidence: 99%
“…Blood samples to determine hydrocodone plasma concentrations were collected from each subject during each of the treatment periods at the following time points: predose and at 0.5, 1, 2. 5,4,6,8,10,12,14,16,18,24,30,36,48, and 72 hours postdose.…”
Section: Study Designs Dose-proportionality Studymentioning
confidence: 99%
“…Review articles have found that, compared with IR formulations, oral ER products produce more consistent plasma concentrations and lower peak-to-trough fluctuations over the dosing interval. 7,8 Additionally, the pharmacokinetic (PK) characteristics of ER products have been found to provide sustained pain relief, with less frequent dosing, reduced pill burden, and more stable clinical effects. [7][8][9] Furthermore, a singleentity ER hydrocodone product may reduce the risks associated with the nonopioid components of the IR products, permitting a higher total daily hydrocodone dose in appropriate patients in whom the benefit/risk balance justifies such a regimen.…”
Section: Introductionmentioning
confidence: 99%